Purine Pathway Implicated in Mechanism of Resistance to Aspirin Therapy: Pharmacometabolomics‐Informed Pharmacogenomics. Issue 4 (11th June 2013) - Yerges‐Armstrong, L M; Ellero‐Simatos, S; Georgiades, A; Zhu, H; Lewis, J p; Horenstein, R B; Beitelshees, A L; Dane, A; Reijmers, T; Hankemeier, T; Fiehn, O; Shuldiner, A R; et al.
<x xml:space="preserve">Abstract</x> Although aspirin is a well‐established antiplatelet agent, the mechanisms of aspirin resistance remain poorly understood. Metabolomics allows for measurement of hundreds of small molecules in biological samples, enabling detailed mapping of pathways involved in drug response. We defined the metabolic signature of aspirin exposure in subjects from the Heredity and Phenotype Intervention Heart Study. Many metabolites, including known aspirin catabolites, changed on exposure to aspirin, and pathway enrichment analysis identified purine metabolism as significantly affected by drug exposure. Furthermore, purines were associated with aspirin response, and poor responders had higher postaspirin adenosine and inosine levels than did good responders (n = 76; both P < 4 × 10−3). Using our established "pharmacometabolomics‐informed pharmacogenomics" approach, we identified genetic variants in adenosine kinase associated with aspirin response. Combining metabolomics and genomics allowed for more comprehensive interrogation of mechanisms of variation in aspirin response—an important step toward personalized treatment approaches for cardiovascular disease. Clinical Pharmacology & Therapeutics (2013); 94 4, 525–532. doi:10.1038/clpt.2013.119